Using Surface Strategy Taxonomy (SST) in Analyzing Students’ Errors in Conducting Recount Paragraph - Meta Keumala; Zahratul Idami (JET ADI BUANA, 2022)
Writing is considered as one of the most complicated skill in English that leads students to do some errors in conducting particular paragraph. This research was conducted to analyze students’ error in writing recount paragraph. A Theory on Surface Strategy Taxonomy (SST) which is proposed by Dulay, Burt, and Krashen (1982) was used to analyze the students’ work. There were 4 types of errors had been classified according to the theory, namely: omission, addition, malformation, and disordering. A qualitative design was administered in conducting this research. Meanwhile, as the data, a 200-to-250-word recount paragraph had written by each of 30 female students of the tenth grade of a Senior High School in Aceh. The findings showed that the most errors made by the students was in the form of disordering for 29,4%; errors in omission for 27,5%; errors in  addition for 21,8%; and errors in malformation for 21,3%. As the conclusion, although errors in writing recount paragraph was something possible to be made by EFL students, to decrease them, the teachers or instructors should facilitate and  expedite EFL classroom with more appropriate and various ways of recount text material learning process.